2021
DOI: 10.1590/1806-9282.20200763
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the use of a physical-activity mobile application on body composition and sleep quality of overweight children

Abstract: OBJECTIVE:To analyze the use of a mobile physical activity application and its influence on body composition and sleep quality in overweight children. METHODS:Prospective study with 37 patients from the Child and Adolescent Obesity Clinic at Unicamp Hospital das Clínicas, between 2018 and 2019. Anamnesis and anthropometry were performed. We oriented the use of the application for six weeks, five days/week for ten minutes.RESULTS: Among 37 patients, 28 (mean age 10.7±2.0 years, 50% boys) used the application. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Muscle mass increased significantly in the experimental group, while in the control group no significant changes were observed. Previous research conducted in overweight children showed similar results, with increases in muscle mass after the use of the app (De Freitas et al, 2021 ). However, both the experimental and control groups presented greater corrected thigh girth, but the change between pre and post measurements was significantly higher in the experimental group.…”
Section: Discussionsupporting
confidence: 71%
“…Muscle mass increased significantly in the experimental group, while in the control group no significant changes were observed. Previous research conducted in overweight children showed similar results, with increases in muscle mass after the use of the app (De Freitas et al, 2021 ). However, both the experimental and control groups presented greater corrected thigh girth, but the change between pre and post measurements was significantly higher in the experimental group.…”
Section: Discussionsupporting
confidence: 71%